1989
DOI: 10.3109/00207458908986252
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Emotional Cues in Patients with Dementia of the Alzheimer's Type

Abstract: Previous research on patients with dementia of the Alzheimer's type (DAT) has focused primarily on intellectual and memory deficits. The present study investigated another aspect of cognitive functioning, that of processing of emotional cues. Subjects included 30 DAT patients and 13 normal controls who were asked to identify emotional expressions in pictured faces and in tone of tape recorded sentences. A battery of neuropsychological tests was also administered. DAT patients were impaired on all tasks as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…Interestingly, fear and disgust may be seen as avoidance-related emotions [42] with their central neural substrates being the amygdala for fear [43] and the insula and the basal ganglia for disgust [4,44]. This interpretation is supported by the finding of a selective FER impairment for fear and contempt [11,24,45]. …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Interestingly, fear and disgust may be seen as avoidance-related emotions [42] with their central neural substrates being the amygdala for fear [43] and the insula and the basal ganglia for disgust [4,44]. This interpretation is supported by the finding of a selective FER impairment for fear and contempt [11,24,45]. …”
Section: Discussionsupporting
confidence: 67%
“…The decrease in FER capacity with increasing cognitive impairment is in part reminiscent of findings of other studies suggesting differences between the normal elderly and those suffering from AD [2,3,10,11,13,15,18], with age being a minor determinant of FER capacity. However, as in our study, decreased FER has not always been observed across all emotions analyzed.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, demented patients' ability of emotion coprehension was defined as their ability of recognizing other people's affects from their facial expressions or from the situations that the others are in. Allender and Kaszniak [2] showed that in patients with dementia of the Alzheimer type (DAT), the ability of emotion comprehension generally deteriorates. DAT and vascular dementia (VD) are the two most common dementias.…”
mentioning
confidence: 99%
“…Other studies [12][13][14] indicate that patients with AD have an impaired capacity to process the facial expressions of emotion, probably due to the characteristic cognitive deterioration associated with the disease, especially in the attention and memory processes of the amygdala [11] and other brain structures that modulate emotional processing [15].…”
Section: Emotions Aging and Dementiamentioning
confidence: 99%